Effects of Harvest Time on the Yield and Forage Value of Winter Forage Crops in Reclaimed Lands of Korea - Yeongmi Jang; Bumsik Choi; Khulan Sharavdorj; Suhwan Lee; Jinwoong Cho (Agriculture, 2022)
This research was conducted to select the most suitable winter forage crop varieties for silage in reclaimed land located in the Midwest of Korea by investigating the soil environment, crop growth characteristics, dry weight, and forage value according to growth stage. The slightly alkalescent soil was characterized by a pH of 7.41–7.84, by an electrical conductivity (EC) of 1–2.5 dS/m, and by 440–934 mg/kg of available phosphate. Barley showed the highest chlorophyll content in the heading stage and milk stages, while oats and triticale reached the highest content in the milk and dough stage. In both years, triticale achieved the highest leaf area index (LAI), reaching 4.3–4.8. In addition, triticale showed the highest percentage of dry matter and the highest dry weight in the milk stage. Forage value was the best in the heading stage for all cereal crops; however, its quality decreased as the growth stage proceeded. This study suggests cultivating triticale, which showed high adaptability to reclaimed soil and climatic conditions, as well as good growth and dry weight when harvested between the milk and dough stages. These results indicate that triticale can be cultivated all year round in salty soil and these data can be useful to increase forage production in reclaimed soil.